Low-Cost Machinery for Better Rural Livelihoods in Tunisia - Rudiger, Udo; Frija, Aymen; Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2023)
The Blog shows how ICARDA's context-adapted technologies and machines significantly improve the livelihoods of dryland small-landholders in the Tunisian Agroecological Living Landscape (Kef-Siliana Transect) – the hardest hit by intensifying climate change and global shocks.